Enhanced lithium-ion battery performance with a novel composite anode: S-doped graphene oxide, polypyrrole, and fumed silica - Al-Bujasim, Mohammed; Gencten, Metin; Donmez, Koray Bahadir; Arvas, Melih B.; Karatepe, Nilgun; Sahin, Yucel (IOP Publishing Ltd, 2025)
In this work, a novel composite anode material was developed, utilizing S-doped graphene oxide (SGO), polypyrrole (PPy), and fumed silica to enhance the performance of lithium-ion batteries (LIBs). The chronoamperometric approach was used to produce SGO, while the chemical method was employed to synthesize PPy. A composite of SGO, PPy, and fumed silica was prepared as an anode for a half-cell, using two samples: one with a high PPy ratio (S1) and the other with a low PPy ratio (S2) and compared the results with bare sample (S0). The S1 sample exhibited a good initial discharge capacity (648 mAh g-1), with capacities of 207 and 131 mAh g-1 at 5 C and 10 C, respectively. S1 and S2 also demonstrated superior cycling stability at a high current (100 cycles at 10 C), with a retention capacity of 99 and 87%, respectively compared with S0 which retained only 68%. Coin-type full cells with S1 as the anode and LiFePO4 (LFP) as the cathode were assembled and compared with commercial graphite anodes. The S1 full cell showed a high reversible capacity (164 mAh g-1 at 0.1 C), with a capacity retention of 66% after 100 cycles at 10 C. At the same time, the graphite anode exhibited a reversible capacity of 133 mAh g-1 at 0.1 C, with a capacity retention of 58% after 100 cycles at 10 C. The S1 full cell achieved a gravimetric energy density of 164 W h kg-1 at 0.1 C and 49 W h kg-1 at 10 C, which is 25% greater than that of the graphite full cell(39 W h kg-1 ) at 10 C. These distinguishing characteristics of S1 make it a viable substitute for graphite as a high-performance anode material in LIBs, opening the possibility for devices with reliable battery systems.
Keywords: Li-ion batteries; anode materials; fumed silica; S-doped graphene; polypyrrole; full cell; CONDUCTING POLYMERS; NANOSHEETS; GRAPHITE; STORAGE; SIO2; Science & Technology - Other Topics; Materials Science; Physics